La Vénus Jōmon, grande oubliée du panthéon des arts japonais ? - Chloé-Alizée Clément (Les Cahiers de l'École du Louvre)
The Jōmon Venus (3500–2400 BCE), a dogū (anthropomorphic clay figurine), is an emblematic work from the Jōmon period (14,000–1st millennium BCE) discovered not far from Nagano in central Japan less than forty years ago. Since then, its significance has changed dramatically: sometimes adored and celebrated, sometimes neglected and forgotten, the Jōmon Venus has had a huge impact in the context of the rise of the Nihonjinron historical school. Its history bears witness to the changes in Japanese cultural policies and identity since the 1980s.